SPARC Overexpression Promotes Liver Cancer Cell Proliferation and Tumor Growth - Gao, Zhao-wei; Liu, Chong; Yang, Lan; He, Ting; Wu, Xia-nan; Zhang, Hui-zhong; Dong, Ke (Frontiers in Molecular Biosciences, 2021)
Background: Secreted protein acidic and rich in cysteine (SPARC) play an important role in cancer development. The roles of SPARC in liver hepatocellular carcinoma (LIHC) are unclear. Methods: GEPIA2 and UALCAN were used to analyze the SPARC mRNA expression levels in LIHC based on TCGA database. GEO database was used to verify the analysis results. Immunohistochemical (IHC) analysis was used to investigate the SPARC protein levels in LIHC tissues. Kaplan-Meier (KM) Plotter was used to analyze the correlation between SPARC and prognosis. Serum SPARC levels were measured by ELISA. CCK8 and murine xenograft models were used to investigate the effect of SPARC on liver cancer growth in vitro and vivo. SPARC correlated genes were screened by LinkedOmics. Results: Based on TCGA and GEO database, the analysis showed that SPARC mRNA expression levels were increased in tumor tissues and peripheral blood mononuclear cell (PBMC) from LIHC compared to normal controls. IHC analysis showed an increased levels of SPARC protein in LIHC tissues compared to adjacent non-tumor tissues. However, we found that the serum SPARC levels were lower in LIHC than that in healthy controls. KM plotter showed that there was no significant correlation between SPARC mRNA levels and overall survival. However, in sorafenib treated LIHC patients, high SPARC expression predict favorable prognosis. Furthermore, the endogenous SPARC overexpression promote liver cancer cells proliferation in vitro and tumor growth in vivo, while there was no significant effect of exogenous SPARC treatment on liver cancer cells proliferation. Function enrichment analysis of SPARC correlated genes indicated a critical role of interaction with extracellular matrix in SPARC promoting cancer cells proliferation. Conclusion: SPARC mRNA were increased in LIHC tumor tissues and SPARC overexpression may promote liver cancer growth. Further studies are needed to clarify the potential prognostic value of SPARC, both in tissues and in circulation.